PENGUATAN PERILAKU ANTI KORUPSI DI LINGKUNGAN BIROKRASI PEMERINTAH PROVINSI RIAU - ', Adlin; Handoko, Tito (Nakhoda: Jurnal Ilmu Pemerintahan, 2018)
Corruption behavior in the Riau Provincial Government?s bureaucracy has been at an alarming stage, this is evidenced by the corruption of the construction of the anti-corruption monument in Riau province, which resulted in the detention of 13 state civil servants and 5 private parties. This study aims to identify factors that can be used as models to strengthen the culture of anticorruption in the Riau provincial government bureaucracy, by examining institutions and individuals within the Riau provincial bureaucracy that are considered to have anti-corruption behavior. This research was conducted with a qualitative method by interviewing officials in the Regional Personnel Agency, Forestry and Environment Agency, Women?s Empowerment Agency, Inspectorate and Riau Province Integrity Strengthening Team. The results of the study show that strengthening anti-corruption behavior in individuals within the institution is supported by three factors, namely the policy of the Riau provincial government, Supervision of law enforcement agencies and strengthening anti-corruption behavior in individual bureaucrats.